Virtual Influencer with Disability: Representation of Inclusion or Exploitation - Wa Ode, Lusianai; Nurfikria, Ikrima; La Ode, Efrianto (Indonesian Journal of Disability Studies, 2024)
In recent years, the virtual world has been filled with virtual influencers (VIs). @itskamisworld is the first VIs with disability as a digital inclusive space for people with disabilities. When VIs are becoming a digital marketing trend and there are allegations of objectification of women's bodies in them, it is important to question the inclusivity and presence of women with disabilities in virtual spaces which in many ways are still marginalized. Using Stuart Hall's representation theory and multimodal discourse analysis on every Instagram post @itskamisworld. The results demonstrated that Kami appears as a form of inclusiveness in the virtual world as well as being a space for advocating the domination of the construction of ideal women by representing perfect women and subjects who actively determine her needs. However, the desires and needs that Kami obtains are only virtual, fantasies that have the potential to become objects of capital exploitation.